Revealing Probiotic Potential of Enterococcus Strains Isolated From Traditionally Fermented Chhurpi and Healthy Human Gut - Ghatani, Kriti; Thapa, Subarna; Sha, Shankar Prasad; Sarkar, Sourav; Modak, Debabrata; Bhattacharjee, Soumen (Frontiers in Microbiology, 2022)
In the present work the two lactic acid bacterial strains Enterococcus durans and Enterococcus lactis previously isolated from soft Chhurpi, a traditionally fermented milk product prepared by the indigenous community of Sikkim Himalayas and healthy human gut were used. In this study we attempted to investigate the probiotic attributes, safety and health beneficial role, hypocholesterolaemia of Enterococcus durans and Enterococcus lactis. Both probiotic potential strains showed good hypocholesterolaemic activity in vitro along with tolerance to acid pH (2 and 2.5), tolerance to three bile salts; oxbile, cholic acid and taurocholic acid (0.5 % and 1 %), presence of BSH enzyme and its activity and cell surface adherence. On assessing for safety both LAB strains were sensitive to antibiotics and exhibited no haemolytic activity. The probiotic strains were tested in vivo in the Sprague Dawley rats which were divided into five experimental groups; Normal Control (ND), probiotic strain Enterococcus durans HS03 (BSH negative) and high cholesterol diet (HCD1), probiotic strain Enterococcus lactis YY1 (BSH positive) and high cholesterol diet (HCD2) and a combination of both strains and high cholesterol diet (HCD3) and Negative Control (HCD). The probiotic treated groups HCD1, HCD2 and HCD3 showed decrease in serum cholesterol levels up to 22.55%, 6.67% and 31.06%, TG and VLDL concentrations were 25.39%, 26.3% and 33.21%, reduction in LDL-cholesterol was 33.66%, 28.50% and 35.87% and increase of HDL was 38.32%, 47.9% and 41.92%. Similarly the effects of total cholesterol and TG in liver, kidney and liver histopathology, liver and body lipid index and oxidative stress in rat liver were also studied. The fecal lactobacilli were more in samples of the probiotic treated groups and their fecal coliform and E. coli counts decreased relatively as compared to control groups in 0,7,14 and 21 days. This is the first report on probiotic potential of Enterococcus durans HS03 and Enterococcus lactis YY1 strains that gives a new insight to the cholesterol lowering and probiotic product development with wide health attributes.